Respuesta :

Answer:

3rd option

Step-by-step explanation:

Given z is inversely proportional to (y - 2)² then the equation relating them is

z = [tex]\frac{k}{(y-2)^2}[/tex] ← k is the constant of proportion

To find k use the condition when y = 5, z = 9 , then

9 = [tex]\frac{k}{(5-2)^2}[/tex] = [tex]\frac{k}{3^2}[/tex] = [tex]\frac{k}{9}[/tex] ( multiply both sides by 9 )

81 = k

z = [tex]\frac{81}{(y-2)^2}[/tex] ← equation of proportion

Try 3rd one that’s the best one on there
ACCESS MORE